2012
DOI: 10.1039/c2gc35564g
|View full text |Cite
|
Sign up to set email alerts
|

One-step hydrogenolysis of glycerol to biopropanols over Pt–H4SiW12O40/ZrO2 catalysts

Abstract: The one-step hydrogenolysis of biomass-derived glycerol to propanols (1-propanol + 2-propanol), which are known as biopropanols, was investigated over different supported Pt-H 4 SiW 12 O 40 (HSiW) bi-functional catalysts in aqueous media. Among the catalysts/supports tested, Pt-HSiW supported over ZrO 2 converted glycerol to biopropanols with high selectivity and high yield (94.1%), while exhibiting long-term stability (160 h). In addition, this catalyst can be resistant to the impurities present in crude glyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
95
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(99 citation statements)
references
References 35 publications
2
95
0
2
Order By: Relevance
“…Indeed, FESEM image reveals that the catalyst morphological characteristics remain unaffected during the reaction due to the good hydrothermal stability of zirconia (confirmed by TGA results). Similar results were also reported elsewhere [34][35][36].…”
Section: Morphological Analysissupporting
confidence: 92%
“…Indeed, FESEM image reveals that the catalyst morphological characteristics remain unaffected during the reaction due to the good hydrothermal stability of zirconia (confirmed by TGA results). Similar results were also reported elsewhere [34][35][36].…”
Section: Morphological Analysissupporting
confidence: 92%
“…In addition, latest progress revealed that ethylene glycol, 1-propanol and 2-propanol can also be obtained from the catalytic hydrogenolysis of glycerol (51). For example, in the presence of Rh/SiO 2 or Pt-H 4 SiW 12 O 40 /ZrO 2 catalysts and hydrogen, a considerable amount of 1-propanol and 2-propanol was yielded in the catalytic hydrogenolysis of glycerol (126,130,131). Particularly interesting is the possibility of obtaining ethylene glycol from glycerol, considering that it is a bio-based feedstock and the resulting ethylene glycol can be used with terephthalic acid in the polyesterification to yield a thermoplastic polyester (polyethylene terephthalate), which is widely used for making synthetic fibers and soft drink bottles.…”
Section: Catalytic Hydrogenolysis Of Glycerol To Propanediolsmentioning
confidence: 99%
“…The main products obtained in glycerol hydrogenolysis are 1-hydroxy-propan-2-one (ACETOL) [14], 1,2-PDO [15], 1,3-PDO [16] and ethylene glycol (EG), the latter involving a C-C cleavage [17]. However, depending on the used catalyst and reaction conditions, other products such as propan-1-ol and propan-2-ol can be obtained in high yields [18]. Selectivity of products can be tuned by using different metals [14], supports [19] or additives [16].…”
Section: Introductionmentioning
confidence: 99%